Pengaruh komitmen pegawai dan kepuasan kerja Terhadap disiplin kerja di Kantor Badan Penelitian Dan Pengembangan Provinsi Riau - Muhammad Ilham Hasbi; Marnis '; Arwinence Pramadewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The aims of this research is to find out the employee commitment and job satisfaction with work discipline. The population of this research is taken from employes of Research and Development of Riau Province Office’s. Total Sampling method is used to get the samples from 80 peoples. To analyze the data Multiple Linier Regression, F- test, and t- test analysis with using SPSS 17. The result shows that employee commitment about value and aim, participatory and loyality in organization are sufficient. Employee job satisfaction show that their statisfied with their Jobs. For employes work discipline is in sufficinet categories. The result shows that both of variabel employee commitment and job satisfaction had significant effects with work discipline. Employee commitment and job satisfaction has positive coefficient regression, in other words employee commitment and job statisfaction will improved work discipline. There are strong correlations between employee commitment and job statisfaction with work discipline.Keywords : Employee Commitment, Job Satisfaction, and Work Discipline